Strategi Pemasaran Sekolah dalam Meningkatkan Minat Peserta Didik pada Yayasan Pendidikan Terpadu Mata Hati di Bandar Lampung - Melan Susanty; Natalia Willianti (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
The Mata Hati Integrated Education Foundation is an inclusive school that provides facilities for parents who need a special school for children with special needs, located at Jln. Mawar No.28-30 Rawa Laut, Bandar Lampung. This study analyzes how marketing strategies are used to increase student interest in the Mata Hati Integrated Education Foundation in Bandar Lampung. The purpose of this study was to find out what strategies were used to increase students' interest in the Mata Hati Integrated Foundation, using qualitative research methods. Data collection techniques are interviews, observation and documentation studies, using marketing mix analysis. The results of the study indicate that the activities carried out to analyze the results of marketing or last year's achievements include the marketing strategy used, promotional media, and the formation of a committee or personnel determination. Keywords : marketing mix, interest, school marketing strategy